Nieznane bagienne miejsce ofiarne z okresu rzymskiego na terenie Wielkopolski - Makiewicz, Tadeusz (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
In the vast literature on Germanic sacrificial rituals, the relevant features and sites, i.e.sacrificial bog places and various deposits, used to be regarded as mostly typical of northern Germany and southern Scandinavia. On the other hand, it has been tacitly assumed that features of this type did not occur in Poland though already E.Blume (1912) had listed numerous finds of this kind among which that at Buczek near Białogard claims special attention. In 1964 1971 a bog site at Otalijżka in Masovia was being examined. The present writer has interpreted it as a typically Germanic sacrificial site and listed numerous sacrificial finds from Poland. Thus any information which can contribute to our knowledge about this category of finds is of great value. Recently, the writer has found data concerning yet another sacrificial bog site located in eastern Great Poland. The relevant data are in the private archive of J. Kostrzewski, in the Archives of the Archaeological Museum in Poznan, and in press notes as well. From these records it follows that in 1937 an archaeological discovery was made during peat digging at the village of Słowikowo (formerly Trzemeszno commune, Mogilno district and at present Konin province). The find consisted of a complete bronze vessel (Fig. 2), 8 silver denarii, „small sheets of old brass vessels”, hazel-nuts, linen textiles, charcoal, numerous animal bones and „pieces of w ood” . Unfortunately, all these objects have been lost and only the photographs of the vessel and coins have survived. The vessels is a bronze cauldron of E40 type and the denarii cover the period from A.D. 98 to 192 (1 of Traian, 2 of Fladrian, I of Sabina, Hadrian’s wife, 2 of Antoninus Pius, 1 of Lucius Verus and 1 of Crispina, Commodus’ wife). The find spot was located in a meadow, 80 by 120 m in size, in a distinct depression shaped as a small cove (Fig. 1) and several metres deeper than the surrounding ground. The materials occurred throughout the length of the peat-ditch, reaching from the ground level to a depth of 3 m. The site, sofar not mentioned in relevant literature, was tentatively interpreted as a pile dwelling. It was intended to start excavation there in the autumn of 1939. In the writer’s view, these data argue against the interpretation of the site as a bog settlement and point to its sacrificial character. This argument is further supported by the location of the site in a marshy area, unsuitable for settlement, and in direct neighbourhood of a zone favourable for habitation. It is quite possible that a lake had still existed there in the Roman period. Moreover, there is not the slightest evidence that bog settlements of any kind did exist in Poland in the Roman period. The set of finds, too, is by no means typical of a settlement. At the same time, the finds are rich, yet they were found by accident by a non-professional who did not attach any importance to the discovery. Certain finds such as hazel-nuts, linen textiles, charcoal (and animal bones as well) are particularly characteristic of sacrificial sites. This is also confirmed by the presence of the cauldron of E40 type. Identical or similar cauldrons (types E38-43) are known from the whole area of central- and north-European barbaricum yet not a single specimen has been recorded in a settlement. On the other hand, they have been revealed on bog sites. Attention should also be drawn to the presence of „small sheets of brass” (i.e. bronze), certainly fragments of other destroyed vessels. The lack of any mention of potsherds, the staple material of any settlement, is also significant. Thus the location and set of finds from Słowikowo unmistakably point to a sacrificial bog site. The location is typical and the relics are characteristic of Germanic sacrificial bog sites though they have a certain specificity. The dating of the assemblage rests on the bronze E40 cauldron from phase B2 of the Roman period and on the silver denarii which range in date from A.D. 98 to 192. Accordingly, it is possible to surmise that the Słowikowo site was being used for a fairly long period in phases B2 and Cl of the Roman period, i.e. from several dozen to about 150 years. The set of finds from Słowikowo differs from that known from other sacrificial sites (naturally, the incompleteness of the available information should be taken into account) though certain elements are especially typical of the sites in question (hazel-nuts, animal bones, textiles). The distinctive characteristic of Słowikowo is the presence of the bronze cauldron and silver coins. On the other hand, we know nothing about the character of timber remains. From all this it is possible to infer a certain variety in the character of sacrificial sites. This is in agreement with current views and has been emphasized by H. Jankuhn according to whom the whole Germany was divided into „cult regions". All this, combined with the evidence from other sites from Poland and with new discoveries of this type from Germany, shows that in the pre- Roman and Roman period sacrificial bog sites of differentiated character were typical of the whole area of central- and north-European barbaricum. At the same time it provides evidence for the uniformity and homogeneity of religious beliefs in that area. It is also possible to assume that sacrificial bog sites were rather a typical than exceptional phenomenon.